Aquatic Sediments Roles of Brantas Watershed Outlet on Availability of Ca2 +, Mg2 +, Na +, K + and Boron in Water Board as Irrigation Water Source - I Made Gede Sudyadnyana Sandhika; Barlah Rumhayati; Atikah Atikah (Natural B, Journal of Health and Environmental Sciences, 2015)
The role of aquatic sediment of outlet DAS Sumber Brantas for the availability of Ca2+, Mg2+, Na+, K+, and boron in water body has been investigated from July-September 2014. Sediment and water samples were collected from the outlet of Sumber Brantas watershed in Arboretum Sumber Brantas village, Batu. This research aim was to investigate the distribution and sediment role for availability of Ca, Mg, Na, K, and boron in water body. The research results show that Ca was the dominant metal ion that was found in water body, while in sediment metal ions that dominant were Ca and Mg. The concentration of metal ion Ca was highest in August with average of concentration 1105.51 ppm and concentration of metal ion Mg was highest in July with average of concentration 1038.94 ppm. Comparison for metal ions concentration in water and sediment shows that sediment had a greater role as a sink for metal ion Ca and boron, while the sediment was a source for metal ions Mg, Na, and K in water body.